Prevalence of death anxiety and its related factors in the population of eastern Iran: a cross-sectional study in the era of COVID-19 - Hossein Bakhtiari-Dovvombaygi; Hossein Bakhtiari-Dovvombaygi; Mohammadreza Askari; Mohammad Rahimkhani; Mahboobeh Abdollahi; Mohammadreza Baladastian; Amir Alipour; Amir Alipour; Mohammad Namazinia (Frontiers in Public Health)
BackgroundThe global COVID-19 pandemic has triggered widespread anxiety, including a significant rise in death anxiety. If unaddressed, death anxiety can lead to numerous mental and physical health issues. This study aimed to assess the prevalence of death anxiety and its associated factors in the population of eastern Iran.MethodsThis cross-sectional study included 515 participants from Torbat Heydariyeh in 2019. Data were collected using a structured two-part questionnaire: demographic data and the Templer Death Anxiety Scale. Sampling was conducted through a stratified approach to represent the city's population distribution accurately.ResultsThe mean age of participants was 32.88 ± 10.75 years (range: 18–80). The mean death anxiety score was 6.72 ± 3.11. Multiple linear regression analysis revealed significant associations between death anxiety and gender (B = 1.12, β = 0.23, P = 0.001), education level (B = 1.75 for high school or lower, β = 0.19, P < 0.05), smoking (B = 0.76, β = 0.15, P = 0.049), and economic status (B = −0.82, β = −0.12, P = 0.006). No significant relationship was found between death anxiety and age, marital status, occupation, medical history, medication use, health status, or income source (P > 0.05).ConclusionsThis study demonstrates that participants exhibited moderate levels of death anxiety. Given its potential to impact quality of life, strategies for managing death anxiety should be considered in similar public health crises.